Giuseppe Maria Crespi e il Gran Principe Ferdinando de' Medici - ZUCCHINI, ELISA (Premio Ricerca «Città di Firenze», 2021)
The iconological analysis of Crespi's paintings for Grand Prince Ferdinando de'Medici reveals shared ideas rooted in Seneca's philosophy, basis of their taste for genre and pastoral scenes. Crespi was a leading figure of the prince's artistic view, according to which arts and sciences guide to wisdom and virtue. Their appreciation for bizarre iconographies and Venetian style painting is clarified by ideas inspired by Seneca on ingenuity and picturesque frenzy. The characteristics of conciseness, brilliance, coexistence of archaism and innovation associate Ferdinando's artistic and musical patronage, influencing his favourite artists and composers and perhaps Handel's art collection.